2005
DOI: 10.1016/j.cbpc.2004.12.006
|View full text |Cite
|
Sign up to set email alerts
|

A novel membrane guanylyl cyclase expressed in medaka (Oryzias latipes) intestine

Abstract: -A novel membrane guanylyl cyclase (GC), OlGC9, was identified in the intestine of the medaka fish Oryzias latipes by the isolation of a full-length cDNA clone

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Indeed, GC-C1 and GC-C2 are two GC-C subtypes so far characterized in the European (Anguilla anguilla) and Japanese eels (11,39,69). Two subtypes, OlGC6 and OlGC9, are also expressed in medaka (Oryzias latipes) (36), while only one GC-C type has been found in mammals and it is the predominant GC in the Values are means Ϯ SE; n ϭ 5-6 for the responses of each anterior and posterior intestinal segment to GN, UGN, and RGN, respectively. Peptides were applied to the mucosal half-chamber (2-ml volume) of an Ussing chamber in a cumulative manner.…”
Section: Tissue-specific Responses To Eel Gn Ugn and Rgnmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, GC-C1 and GC-C2 are two GC-C subtypes so far characterized in the European (Anguilla anguilla) and Japanese eels (11,39,69). Two subtypes, OlGC6 and OlGC9, are also expressed in medaka (Oryzias latipes) (36), while only one GC-C type has been found in mammals and it is the predominant GC in the Values are means Ϯ SE; n ϭ 5-6 for the responses of each anterior and posterior intestinal segment to GN, UGN, and RGN, respectively. Peptides were applied to the mucosal half-chamber (2-ml volume) of an Ussing chamber in a cumulative manner.…”
Section: Tissue-specific Responses To Eel Gn Ugn and Rgnmentioning
confidence: 99%
“…intestine (4). Nonetheless, stimulation of fish and mammalian GC-Cs expressed in cell culture lines by GN or UGN leads to significant guanylyl cyclase activity and increases in cGMP (10,13,15,36,53,69), yet, in the anterior intestine of marine teleosts, these increases may not be occurring in significant amounts (if at all) to produce the downstream effects observed in the posterior intestine.…”
Section: Tissue-specific Responses To Eel Gn Ugn and Rgnmentioning
confidence: 99%
“…Functional expression studies showed that exposure of cells expressing these GC-C-like proteins to the three eel guanylins induced dosedependent increases in cGMP accumulation with different potencies. At least two cDNAs encoding GC-C receptors are cloned in medaka (Mantoku et al, '99;Iio et al, 2005) and their orthologs can be identified in the genome database of pufferfish. Thus, the guanylin system may have diversified into multiple ligands and receptors in teleost fishes, particularly in the eel that has extraordinary osmoregulatory ability.…”
Section: Guanylin Familymentioning
confidence: 99%
“…In addition to the two medaka fish homologues (OlGC2 and OlGC7) of mammalian GC-A (Yamagami et al, 2001(Yamagami et al, , 2003 and one medaka fish homologue (OlGC1) of mammalian GC-B (Takeda and Suzuki, 1999), we have isolated another full-length cDNA clone encoding a medaka fish homologue of mammalian STa/guanylin receptor/GC-C and designated it OlGC9 (Iio et al, 2005). Therefore, medaka fish has two different genes, OlGC6 and OlGC9, whose translating products belong to the STa/guanylin receptor/GC-C subfamily.…”
Section: How Many Gc Members Does Medaka Fish Have?mentioning
confidence: 99%
“…Since then, it has been demonstrated that the α 1 and β 1 subunit genes are aligned in a tandem fashion separating by only a 1 kbp spacer sequence on the medaka fish genome (Mikami et al, 1999). OlGC6 and OlGC9, medaka fish homologues of mammalian -C (Mantoku et al, 1999;Iio et al, 2005), and OlGC1, a medaka fish homologue of mammalian GC-B, have been identified, and their complete nucleotide sequences of genomic DNAs have been determined (Mantoku et al, 1999;Takeda and Suzuki, 1999).…”
Section: Introductionmentioning
confidence: 99%